New Brand Ride-Hailing Apps Continuance Intention of Gen Z: the Role of Personal Innovativeness in Information Technology - Lattu, Arny; Maulana, Agung; Putra, Bagja Rahma (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2023)
The tight competition in the ride-hailing service industry has made Super App digital companies in Indonesia vie to attract public interest to become their regular customers. As new players, Super App Maxim and/or InDriver companies need insight into what factors can make their applications accepted by Generation Z as the largest consumers in Indonesia. So, this study aims to investigate the role of performance and expectations of effort and social influence on continuing intentions to use new online transportation applications through the mediating role of personal innovation in information technology (PIIT). This study used the SEM technique with the SMART PLS 3.3.0 application, with 553 respondents using Maxim and/or InDriver. The study results show that performance, effort expectations, and social influence significantly affect the intention to use online transportation applications. Expected effort is the most significant factor affecting PIIT and intention to continue, followed by social influence and performance expectations. Keywords : Continuance Intentions; Generation Z; Personal Innovativeness In Information Technology; Ride-Hailing Apps, UTAUT